2012
DOI: 10.4238/2012.july.10.17
|View full text |Cite
|
Sign up to set email alerts
|

Integrated statistical learning of metabolic ion mobility spectrometry profiles for pulmonary disease identification

Abstract: ABSTRACT. Exhaled air carries information on human health status. Ion mobility spectrometers combined with a multi-capillary column (MCC/IMS) is a well-known technology for detecting volatile organic compounds (VOCs) within human breath. This technique is relatively inexpensive, robust and easy to use in every day practice. However, the potential of this methodology depends on successful application of computational approaches for finding relevant VOCs and classification of patients into disease-specific profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 13 publications
0
51
0
Order By: Relevance
“…An early diagnosis of COPD would be an advantage. Multiple research groups demonstrated that VOC profiles could accurately differentiate COPD patients from healthy (non-) smokers [25,29,31,33]. In contrast, others found a limited performance of VOCs profiles to differentiate COPD patients from (former) smokers [15,26].…”
Section: Resultsmentioning
confidence: 99%
“…An early diagnosis of COPD would be an advantage. Multiple research groups demonstrated that VOC profiles could accurately differentiate COPD patients from healthy (non-) smokers [25,29,31,33]. In contrast, others found a limited performance of VOCs profiles to differentiate COPD patients from (former) smokers [15,26].…”
Section: Resultsmentioning
confidence: 99%
“…20 Chronic obstructive pulmonary disease (COPD) is an inflammatory condition characterized by oxidative stress and particular VOCs from lungs ( Figure 3). 6 Hauschild et al 4 analysed breath data by IMS-MCC from 84 volunteers, either healthy or suffering from COPD or bronchial carcinoma and extracted 28-scoring VOCs that allowed differentiating COPD patients. On the other hand, Basanta et al 21 used differential mobility spectrometry (DMS) to discriminate between individuals with and without COPD.…”
Section: Applications Of Breath Diagnosis In Medicinementioning
confidence: 99%
“…Like the study of Westhoff et al [66], the advanced pre-processing and peak location methods provided by the VisualNow software were used to build the features for COPD and bronchial carcinoma prediction. To get a broad overview of the potential of the data and the different classification techniques, six different sophisticated statistical learning methods have been applied: Decision trees, naive Bayes, neural networks, random forest and linear as well as radial SVM [79]. Similar to the previous studies of Baumbach et al [78] and Westhoff et al [66], the set of samples was small (119 volunteers), which leads to a very noisy estimation of the predictive performance.…”
Section: Statistical Learningmentioning
confidence: 99%
“…In fact, most of the measurements of COPD patients falsely predicted suffering from both COPD and bronchial carcinoma, which might be reducible to the characteristic of COPD as a common and important independent risk factor for lung cancer. Both studies, Westhoff et al 2011 [66] as well as Hauschild et al [79], identified a set of ten most informative features, whereby five of these twenty features overlapped in the inverse drift time as well as retention time, which means they represent the same VOCs. …”
Section: Statistical Learningmentioning
confidence: 99%